2016
DOI: 10.1021/acs.jpclett.6b00765
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Magnetic Dipole Spectroscopy

Abstract: Pulse electron paramagnetic resonance measurements of nanometer scale distance distributions have proven highly effective in structural studies. They exploit the magnetic dipole-dipole coupling between spin labels site-specifically attached to macromolecules. The most commonly applied technique is double electron-electron resonance (DEER, also called pulsed electron double resonance (PELDOR)). Here we present the new technique of laser-induced magnetic dipole (LaserIMD) spectroscopy based on optical switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
80
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 59 publications
1
80
2
Order By: Relevance
“…In parallel, combining the nitroxide and the endogenous probe in an orthogonal labelling approach has proven to be very effective since the spectroscopically non-identical labels can be addressed selectively during the PDS experiment. [30] However, no triplet state was observed by EPR spectroscopy, as expected for a low-spin ferric heme. [35][36][37][38] Recently, it has been shown that the RIDME experiment is better suited than DEER for distance measurements between spin active moieties with different spin-lattice relaxation times or species with very broad spectra such as metal ions like low-spin Fe(III).…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…In parallel, combining the nitroxide and the endogenous probe in an orthogonal labelling approach has proven to be very effective since the spectroscopically non-identical labels can be addressed selectively during the PDS experiment. [30] However, no triplet state was observed by EPR spectroscopy, as expected for a low-spin ferric heme. [35][36][37][38] Recently, it has been shown that the RIDME experiment is better suited than DEER for distance measurements between spin active moieties with different spin-lattice relaxation times or species with very broad spectra such as metal ions like low-spin Fe(III).…”
mentioning
confidence: 76%
“…[24] One important new development is the demonstration that the triplet state of porphyrin chromophores can be exploited to determine inter-spin distances. [30] Comparison between the two techniques was carried out both at X-band and at Q-band. [25,26] The large electron spin polarization of the photoexcited triplet state, [27,28] and the consequently high sensitivity of the experiment, furthermore allowed light-induced PDS methodology to be applied to a photosynthetic protein, containing an endogenous carotenoid triplet state probe.…”
mentioning
confidence: 99%
See 3 more Smart Citations